Partnership Program on Bali Cattle Fattening Based on Local Resources in the Suboptimal Land Area of Nusa Tenggara Timur - Priyono Priyono; Dwi Priyanto (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2018)
Bali cattle is one of the Indonesian germplasm that well adapted to suboptimal areas including East Nusa Tenggara (NTT). Difficulties in accessing capital became one of the factors that hamper effort the development of Bali cattle in larger scale. One alternative to access capital is through partnership model of Bali cattle fattening based on local resources. Partnership model of Bali cattle fattening was intiated by village cooperative centre (pusat koperasi unit desa =PUSKUD) since 2002 in Kupang District, South Central Timor District, North Central Timor District, and Belu District. Profit sharing in this program is 70% for farmers and 30% for PUSKUD NTT. The partnership program has been performing well and growing rapidly. On the other hand, some problems occurred such as cattle death and forced sale due to lack of feed, especially during dry season. In its development, the partnership model has resulted in empowering farmers through increasing income and employment.